Influence of concentration, nanoparticle size, beam energy, and material on dose enhancement in radiation therapy. (17th April 2017) - Hwang, Chulhwan; Kim, Ja Mee; Kim, JungHoon
Abstract: The purpose of this study was to analyse the effects of the type, concentration, and nanoparticle diameter of dose enhancement materials on the dose enhancement of low- and high-energy megavoltage (MV) X-rays acquired from a medical linear accelerator using Monte Carlo simulation. Monte Carlo simulation was performed with the Monte Carlo N-Particle Transport (MCNPX) code, using the energy spectrum of the linear accelerator and a mathematical Snyder head phantom. A 5-cm-diameter virtual tumour was defined in the centre of the phantom. Gold, gadolinium, iodine and iron oxide were used as dose enhancement materials. Varying concentrations (7, 18 and 30 mg/g) of nanoparticles of different diameters (25, 50, 75, 100 and 125 nm) were applied, and the dose enhancement was comparatively evaluated for 4, 6, 10 and 15 MV X-rays, and a 60 Co source. Higher dose enhancement factors (DEFs) were observed when the incident energy was low. Moreover, the dose enhancement effects were greatest with gold nanoparticles, followed by gadolinium, iodine, and iron oxide nanoparticles; the DEFs were 1.011–1.047 (gold), 1.005–1.030 (gadolinium), 1.002–1.028 (iodine) and 1.002–1.014 (iron oxide). The dose enhancement effects increased with increasing nanoparticle diameter and concentration. However, the concentration of the material had a greater impact than the diameter of the nanoparticles. As the concentration and diameter of nanoparticles increased, the DEF also increased. The 4 and 6 MV X-rays demonstrated higher dose enhancement compared with the 10 and 15 MV X-rays.